Actual evapotranspiration dominated net primary productivity loss caused by concurrent droughts - Zice Ma; Donghua Chen; Peng Sun; Yufeng Liu; Lizao Ye (Ecological Indicators)
Drought profoundly affects terrestrial ecosystem (TE) carbon cycling, but the impact of concurrent droughts (CDs) remains poorly understood. Using Net Primary Productivity (NPP), Standardized Precipitation Evapotranspiration Index (SPEI), Standardized Soil Moisture Index (SSMI), and Standardized Concurrent Drought Index (SCDI) (1982–2022), we analyzed trends and quantified drought impacts on global NPP loss. Our study further quantified the effects of three drought categories on global NPP loss. The findings suggest that NPP has generally decreased across the southern hemisphere, particularly in subtropical Evergreen Broadleaf Forest (EBF) ecosystems (−3.14 gC m−2 yr−1). Zones exhibiting a noticeable decline in NPP often correspond with a decrease in both SPEI and SSMI, leading to an upward trend where 32.4 % of TE experience CDs. Further analysis revealed that CDs have dominated NPP changes in approximately 48.5 % of the global ecosystem. This contributes to an average NPP loss of approximately 15.03 gC m−2 yr−1 in global TE. Random Forest experiments identified ET as the dominant hydrothermic factor of NPP loss under CDs, particularly in forest ecosystems where the importance scores range from 23.0 % to 37.0 %. Our findings underscore the significance of ET anomalies in NPP loss resulting from CDs, providing scientific evidence for addressing ecological risks under climate change.